Transitioning to accrual accounting in the public sector - Zoran Minovski; Jesse Hughes; Aleksandar Kocevski (Journal of Contemporary Economic and Business Issues, 2016)
Public sector entities' aim is to provide services to their citizens. They operate in a specific environment and thus, their accounting system differs from the one used by business enterprises, and its development moves towards greater achievement of the international financial communication, in terms of comparing financial statements between various governments. The purpose of this research paper is to give insight into the current state and the perspectives for further development of the public sector's accounting system over the implementation of the accrual-based accounting in order to reach further harmonization and unification of financial reporting and thus comparability of public sector's results in different countries, a much better understanding of financial statements, and taking further measures and making decisions based on results. Accrual accounting provides a comprehensive view of a government's assets and liabilities, and of its financial performance and cash flows for the period under review. Accrual accounting standards reflect the long-term economic impact of political decisions reflected in financial statements.
Keywords: F53; H11; H83; M41; M48; 330; public sector; accrual accounting; International Public Sector Accounting Standards; Government Financial Systems Manual; International Financial Reporting Standards; Conceptual Framework